The Influence Of Brand Image And Price On Decisions To Purchase Make Over Cosmetics In Medan City - Sitorus, Mayglenn Gracesisilia; Harahap, Kartini (Paspama Institute, 2023)
This research aims to determine the influence of brand image and price on purchasing decisions for Make Over cosmetics partially and simultaneously. This research uses quantitative methods with a literature review design. The population in this study were consumers of Make Over cosmetics in Medan City. In this study, the sample used was 100 Make Over cosmetics users. The data used is primary data by distributing questionnaires via Google Form and secondary data obtained through journals and articles related to my research. The results of this research show that the brand image and price variables significantly influence purchasing decisions.